2012
DOI: 10.12669/pjms.291.2865
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stool antigen test with gastric biopsy for the detection of Helicobacter Pylori infection

Abstract: Objective: Helicobacter Pylori (H.pylori) is one of the most important causes of dyspepsia and diagnosis can be made by invasive or non-invasive methods. One of the non-invasive methods, H.pylori stool antigen test (HpSA) is simple, fast and relatively inexpensive. According to this view with regard to gastric biopsy as a gold standard the sensitivity, specificity, positive and negative predictive values of this method were calculated. Methodology: Stool samples of 61 patients who underwent upper endoscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 4 publications
(6 reference statements)
4
11
0
Order By: Relevance
“…Consistent with the former studies (16,(19)(20)(21)(22)(23)(24)(25), the current study found that HpSA test was sensitive, specific, and accurate to diagnose Hp infection (sensitivity: 80.4%, specificity: 85.7%). To avoid false negative results, which would be achieved if there was a history of chronic liver diseases (eg, cirrhosis), gastrointestinal bleeding, and antacid medications, the patients undergoing proton pump inhibitor or bismuth therapy were excluded.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the former studies (16,(19)(20)(21)(22)(23)(24)(25), the current study found that HpSA test was sensitive, specific, and accurate to diagnose Hp infection (sensitivity: 80.4%, specificity: 85.7%). To avoid false negative results, which would be achieved if there was a history of chronic liver diseases (eg, cirrhosis), gastrointestinal bleeding, and antacid medications, the patients undergoing proton pump inhibitor or bismuth therapy were excluded.…”
Section: Discussionsupporting
confidence: 90%
“…The diagnostic values for HpSA in the study of Sharbatdaran et al 17 using polyclonal technique were 66%, 93%, 91% and 62%, respectively. Syam et al 21 also observed that HpSA when using polyclonal technique has sensitivity of 66.7% and specificity of 78.9%.…”
mentioning
confidence: 85%
“…1 There are studies evaluating the accuracy of HpSA for detection of H. pylori in children 14,15 and hemodialysis patients, 12,16 but studies about HpSA accuracy in adults with GI complaints in Iran are few. 10,11, 17 Here, we examined the role of HpSA in diagnosing H. pylori infection in patients with upper GI complaints. In this prospective study, H. pylori infection was evaluated using HpSA in patients with upper GI complaints undergoing diagnostic endoscopy.…”
mentioning
confidence: 99%
“…Anyway, precipitates or striae of mucous covering without regular bacterial contour, and neither gray staining for H & E stain nor dark blue staining for Giemsa stain should not be interpreted as low or trace HP density. Otherwise, these over interpretations of so called gold standard might reflect in appropriate lower sensitivity of other HP tests such as stool antigen test in some nations [16,17] comparing with that of another nation [18]. More expensive HP Immunohistochemical (IHC) stain can reduce false positive or false negative results dramatically [19].…”
Section: Resultsmentioning
confidence: 99%